2019
DOI: 10.1111/hex.12934
|View full text |Cite
|
Sign up to set email alerts
|

Co‐producing knowledge of lesbian, gay, bisexual, trans and intersex (LGBTI) health‐care inequalities via rapid reviews of grey literature in 27 EU Member States

Abstract: Background The health inequalities experienced by lesbian, gay, bisexual, trans and intersex (LGBTI) people are well documented with several reviews of global research summarizing key inequalities. These reviews also show how the health‐care needs of LGBTI people are often poorly understood whilst suggesting that targeted initiatives to reduce inequalities should involve LGBTI people. Objectives To determine what is known about the health‐care inequalities faced by LGBTI people? What are the barriers faced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
(151 reference statements)
1
13
0
Order By: Relevance
“…Where this is unattainable and LGBTI research includes people with intersex variance, their goals should be actively prioritised in the research [ 4 ]. Co-producing research with peers who have experiential knowledge and lived experience should be a priority, by involving people with intersex variation at every level from conception, design to undertaking the research [ 2 ]. This kind of research should co-constitute materiality with more intersubjective methodologies and ethically accountable healthcare practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Where this is unattainable and LGBTI research includes people with intersex variance, their goals should be actively prioritised in the research [ 4 ]. Co-producing research with peers who have experiential knowledge and lived experience should be a priority, by involving people with intersex variation at every level from conception, design to undertaking the research [ 2 ]. This kind of research should co-constitute materiality with more intersubjective methodologies and ethically accountable healthcare practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent global public health research reflects significant health inequalities for lesbian, gay, bisexual, trans and intersex (LGBTI) people compared to the general population. Large scale international reviews collating these research findings include studies of LGBTI health inequalities [ 1 , 2 ], the disease burden in gender and sexual minorities [ 3 ], intersex health [ 4 ], the global health burden and needs of transgender populations [ 5 ], the health profile of sexual minority women [ 6 ], and more recently, loneliness and social support in older LGB communities [ 7 ]. These studies share a common denominator of an increasing concern over how diverse identities and bodies intersect and experience health inequalities in LGBTI populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In others, they were identified as members of a panel or advisory council. Some studies identified partner as members of a panel or advisory group; in 11% (n=4) of the articles, a panel or other body was named as an author rather than individual contributors [14,[33][34][35]. Finally, in 27% (n=10) of articles, it was either impossible or difficult to tell whether an author was a partner solely from the affiliation, and confirmation was found elsewhere in the article.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Recognizing partners as authors indicates that they had substantial involvement in the research; however, partners may not accept or receive authorship for various reasons. For instance, the authors may want to preserve their anonymity, as was noted in the review by Sherriff et al [35], where the coauthor was a collective entity (Health4LGBTI Network) and individuals were not named. Furthermore, many health journals require authors to meet the 4 ICMJE criteria, and some partners may be unable or unwilling to fulfill all of these criteria [66,67].…”
Section: Authorship Versus Acknowledgmentmentioning
confidence: 99%